2020
DOI: 10.1016/j.cell.2020.05.021
|View full text |Cite
|
Sign up to set email alerts
|

Major Impacts of Widespread Structural Variation on Gene Expression and Crop Improvement in Tomato

Abstract: Highlights d Long-read sequencing of 100 tomato genomes uncovered 238,490 structural variants d Transposons underlie many SVs, and SV hotspots revealed large introgressions d SVs associated with genes are predictive of population-scale changes in expression d New genome assemblies resolved complex breeding QTLs caused by SVs

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
576
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 597 publications
(664 citation statements)
references
References 99 publications
27
576
0
Order By: Relevance
“…These gains will in turn translate to cost savings for resequencing and validation experiments. Indeed, SVCollector has already been applied to larger sequencing projects such as a detailed study of 11 human genomes and 100 tomato genomes sequenced with long reads (Shafin et al 2020;Alonge et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…These gains will in turn translate to cost savings for resequencing and validation experiments. Indeed, SVCollector has already been applied to larger sequencing projects such as a detailed study of 11 human genomes and 100 tomato genomes sequenced with long reads (Shafin et al 2020;Alonge et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Because of their importance for plant development, it is also possible that FUL-like genes have played a role during tomato domestication. This has already been unveiled for the MADS-box genes JOINTLESS 2 (J2, also called SlMBP21), ENHANCER OF JOINTLESS2 (EJ2/MADS1, hereafter called EJ2) and SISTER OF TOMATO MADS-box gene 3 (STM3) (Roldan et al, 2017;Soyk et al, 2017;Soyk et al, 2019;Alonge et al, 2020). The expression of FUL1, FUL2 and MBP20 is strongly upregulated during the transition from shoot apical meristem (SAM) to inflorescence-and floral meristem (IM and FM) (Park et al, 2012), suggesting that these genes may function in inflorescence meristem development like their Arabidopsis homolog.…”
Section: Introductionmentioning
confidence: 93%
“…Our screen showed that the SlFUL proteins could interact with nine other tomato MADS-domain proteins, and we observed clear differences between the interaction profiles of FUL1, FUL2, MBP10 and MBP20. All FUL-like proteins interacted with JOINTLESS (J), J2 (or SlMBP21, hereafter called J2), the fruit ripening regulator MADS-RIN, and TOMATO MADS 3 (TM3), the ortholog of the Arabidopsis flowering integrator SOC1 (Alonge et al, 2020). FUL2 exhibits the most extensive interaction network, interacting with nine proteins.…”
Section: Expression Patterns and Protein-protein Interaction Profilesmentioning
confidence: 99%
See 2 more Smart Citations